Dietary fibres from guavira pomace, a co-product from fruit pulp industry: Characterization and cellular antioxidant activity. (June 2020) - Schneider, Vanessa Suzane; Bark, Juliana Müller; Winnischofer, Sheila M.B.; Dos Santos, Elisvânia Freitas; Iacomini, Marcello; Cordeiro, Lucimara M.C.
Graphical abstract: Highlights: Guavira pomace is an agroindustrial waste of guavira pulp industry. It was a source of arabinan, homogalacturonan and arabinogalactan. These dietary fibres were able to scavenge ABTS radicals. Dietary fibres protected murine fibroblasts against H2 O2 -induced toxicity. Guavira pomace is a valuable source of antioxidant dietary fibres. Abstract: Exotic fruits and their co-products may be valuable sources of antioxidant dietary fibres (DF) which are useful for food industry and human health. In this study, we aimed to characterize DF obtained from guavira fruit pomace and investigate its antioxidant potential employing TEAC assay as well as a cell model. The DF were chemically characterized as containing arabinan, highly-methoxylated homogalacturonan and arabinogalactan. The DF-containing fraction (CPW) presented ABTS free radical scavenger activity. MTT and DCFH-DA assay were performed to assess, respectively, changes in cell viability and the potential intracellular antioxidant activity against H2 O2 -induced oxidative stress in murine NIH 3T3 fibroblast. CPW exhibited no effects on cell viability, moreover, when administered 48 h prior the induction of H2 O2 toxic effects, it protected the cells, significantly increasing the cell viability compared to control. This protection may be related to the observed reduction of reactive oxygen species levels. Thus, the pre-treatment of cells with guavira DF for 48 h remarkably induced a cytoprotection against pro-oxidant conditions, and may be a valuable functional compound recovered from an unexploited agroindutrial waste.